1996
DOI: 10.1002/pro.5560050709
|View full text |Cite
|
Sign up to set email alerts
|

A recipe for designing water‐soluble, β‐sheet‐forming peptides

Abstract: Based on observations of solubility and folding properties of peptide 33-mers derived from the &sheet domains of platelet factor-4 (PF4), interleukin-8 (IL-8), and growth related protein (Gro-a), as well as other 6-sheet-forming peptides, general guidelines have been developed to aid in the design of water soluble, self-association-induced 0-sheet-forming peptides. CD, 'H-NMR, and pulsed field gradient NMR self-diffusion measurements have been used to assess the degree of folding and state of aggregation. PF4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
105
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(116 citation statements)
references
References 76 publications
11
105
0
Order By: Relevance
“…A shoulder on the near-UV side of the main band appears to account for the 20% or so dimer (p-sheet) present. Present CD data also explain why earlier CD results on ppep-4 (Mayo et al, 1996) showed nearly equally intense CD bands at 204 nm and 217 nm. In that study, CD data were acquired using a peptide concentration of 0.1 1 mM [not the 10-20 mM as stated in the Figure 8 legend (erratum)].…”
Section: Kh Mayo and E Ilyinasupporting
confidence: 82%
See 1 more Smart Citation
“…A shoulder on the near-UV side of the main band appears to account for the 20% or so dimer (p-sheet) present. Present CD data also explain why earlier CD results on ppep-4 (Mayo et al, 1996) showed nearly equally intense CD bands at 204 nm and 217 nm. In that study, CD data were acquired using a peptide concentration of 0.1 1 mM [not the 10-20 mM as stated in the Figure 8 legend (erratum)].…”
Section: Kh Mayo and E Ilyinasupporting
confidence: 82%
“…aH resonances result from formation of well-folded P-sheet sandwich tetramers (Mayo et al, 1996;Ilyina et al, 1997aIlyina et al, , 1997b. As the ppep-4 peptide concentration is lowered at either temperature ( Fig.…”
mentioning
confidence: 99%
“…Fewer proteins have been designed with the P-sheet as the main element of secondary structure (Kullmann, 1984;Moser et al, 1985;Osterman & Kaiser, 1985; Richardson et al, 1992;Pessi et al, 1993; Quinn et al, 1994;Wagner et al, 1994;Krause et al, 1996;Mayo et al, 1996;Nesloney & Kelly, 1996;Smith & Regan, 1997; Zappacosta et al, 1997). Because P-sheets are less modular than a-helices and tend to aggregate in solution, it is more Reprint requests to: Bruce W. Erickson, Department of Chemistry, The University of North Carolina at Chapel Hill, Chapel Hill, North Carolina 27599-3290; e-mail: bruce@peptide.chem.unc.edu.…”
Section: Introductionmentioning
confidence: 99%
“…Our data demonstrate a clear role for the thiol of the Cys side chain in promoting/stabilizing the conformation of the glycopeptides via disulfide-linked dimer formation. Indeed, a known strategy for stabilization of designed β-sheetforming peptides in aqueous solutions involves dimerization (face-to-face or edge-to-edge) and intermolecular disulfide linkage (29)(30)(31)(32)(33), so the observed secondary-structure preferences could very well be due to a similar phenomenon. In our case, the best results were obtained when the oxidative dimerization was performed in aqueous DMSO.…”
Section: Discussionmentioning
confidence: 99%